Exploring the Risks Faced by Hotel Kitchen Professionals: From Stovetop to Safety Net - Rajashree S. Kini; Tantri Keerthi Dinesh; Ankitha Shetty; Ashalatha K (Cogent Social Sciences)
This review is the first to highlight the significant factors contributing to injuries and fatalities in hotel kitchens. It synthesizes measures for enhancing safety and preventing hazards in job contexts with high risk. A systematic literature review following PRISMA guidelines and PECOS was conducted from 2013 to 2023, incorporating 17 empirical studies. The CASP tool was applied to assess study quality, focusing on kitchen professionals’ routine tasks. The findings reveal key risk factors, including the cooking process, machinery and tools, work experience, burns and cuts, mental stress, long hours, production speed, musculoskeletal disorders, awkward postures, kitchen layout, floor type, lifting weight, education level, shift work, sleep disorders, sensation‑seeking behavior, and failure to comply with safety protocols. The study underscores the importance of wellness programs in mitigating these risks. The outcomes provide valuable insights into safety protocols that can reduce kitchen accidents in the hotel industry. By addressing these concerns, the study emphasizes the need for a strong safety culture and effective intervention programs to foster organizational growth while ensuring the well‑being of kitchen professionals.